Community Engagement in Support of Moving Toward Universal Health Coverage - Pascale Allotey; David T. Tan; Thomas Kirby; Liza Haslan Tan (Taylor & Francis Group, 2019)
Community engagement describes a complex political process with dynamic negotiation and renegotiation of power and authority between providers and recipients of health care in order to achieve a shared goal of universal health care coverage. Though examples exist of community engagement projects, there is very little guidance on how to implement and embed community engagement as a concerted, integrated, strategic, and sustained component of health systems. Through a series of case studies, this article explores the factors that enable community engagement particularly with a direct impact on health systems.